Bebedouro refrigerado tipo Nipple para criação animal utilizando Efeito Peltier - Rufino, Carlos Antonio (2016)
This paper presents the development and evaluation of three systems using the thermoelectric effects, and two of them use the principle operating the Peltier chosen, and the third system uses the Seebeck effect. The the first two, is aimed at cooling the animals drink water, If, birds, but using a different design, the first system consists of a nipple drinker with localized cooling, whereas the second system uses a chilled sleeve for cooling zones distributed along the main pipe feeding the animals drinking water. The first two works are titled respectively: ”Trough Cooled Type Nipple for Animal Creation Using Peltier Effect” and ”Refrigerated glove used in Livestock Using Peltier Effect”. The third consists of a direct conversion system of thermal energy into electrical energy, titled ”Electric Power Generation System from photovoltaic cells”. To Cooling system type nipple evaluated the average of the deviation values between the internal temperature of the cooling water measured and the setpoint variation 0:4 C. Refrigerated glove to the results obtained show that the same without insulation in the water supply pipe, the temperature of the first zone measurement and the fifth measurement zone had a temperature range between 18 and 23 C, showing that a reduction in the average internal temperature of water at 3 C manifold, which is a distance between the cooling sleeve and fifth measuring zone 1.5 m. The result obtained for the ”Generation System Electricity from thermovoltaic Cells” allow us to conclude that the use of Peltier cells for power generation at low power with average yield around 25% is feasible, demonstrating the feasibility of the direct conversion of thermal energy into electricity.